Mechanisms of recruitment into sex trafficking operations: a systematic review - Martin, Lauren (Global crime, 2023)
Sex trafficking is a global human rights issue and a form of violence with numerous health and mental health sequelae. This systematic review synthesised the global literature on recruitment into sex trafficking to describe what we know and identify gaps. We identified 5,526 articles, subjected 340 to full-text review, and only 34 met inclusion/exclusion criteria. We found that the empirical literature on recruitment into trafficking is unclear and many studies lack empirical rigour. The literature base lacks detail about tactics employed in the initial recruitment phase and does not differentiate between recruitment and ongoing control of victims. There are many studies on trafficking vulnerabilities, but the literature is weak on how and when traffickers leverage vulnerabilities, and how structural conditions shape effectiveness of trafficking recruitment mechanisms in particular settings. This systematic review highlights a need for more targeted research on the initial recruitment phase of trafficking and research with traffickers.